The efficacy and safety of acetylcysteine combined with budesonide nebulization in treating mycoplasma pneumonia in children: a meta-analysis - He, Yinan; Huang, Rongmei (Frontiers in Pediatrics, 2025)
BackgroundThe aim of this meta-analysis was to systematically evaluate the clinical efficacy and safety of acetylcysteine combined with budesonide nebulization in treating Mycoplasma pneumonia in children.MethodsWe systematically searched eight electronic databases for randomized controlled trials (RCTs) evaluating the use of acetylcysteine combined with budesonide nebulization in treating Mycoplasma pneumonia in children, from database inception through December 2024, and performed data analysis using a random-effects model.ResultsThe 29 RCTs involving 4,300 children were conducted. The experimental group received acetylcysteine plus budesonide treatment, while the comparison group received budesonide alone. Results showed the experimental group had a significantly higher overall clinical efficacy rate (RR = 1.16, 95% CI = 1.13–1.20, I2 = 16%). The experimental group also had a significantly lower incidence of diarrhea (RR = 0.17, 95% CI = 0.05–0.54, I2 = 0%), with no significant difference in other adverse events. The experimental group had significantly shorter times to resolution of cough (SMD = −2.11, 95% CI = −2.65 to −1.57, I2 = 97%), moist rale (SMD = −1.91, 95% CI = −2.50 to −1.33, I2 = 97%), and fever (SMD = −1.70, 95% CI = −2.26 to −1.14, I2 = 95%). Post-treatment, the experimental group had significantly lower C-reactive protein levels (SMD = −1.44, 95% CI = −1.92 to −0.97, I2 = 91%).ConclusionCompared with budesonide monotherapy, acetylcysteine combined with budesonide significantly improved the clinical efficacy in children with Mycoplasma pneumonia while not increasing the risk of adverse events, and represents a safe and effective treatment option.